Hemangioma. A model for the study of the regulatory factors of angiogenesis. - Colonna, V.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
Hemangioma is a benign proliferation of angiopoietic cells. It is characterized by an initial rapid growth followed by a slow involution. Both the phases are regulated by a series of factors that stimulate and inhibit angiogenesis. This is why hemangioma represents a unique model for the study of the factors regulating angiogenesis.The factors promoting and inhibiting angiogenesis are reviewed emphasizing their relationship with hemangioma.